Local Method in Rarefied Gas Aerodynamics - Barantsev, R.G. (Engineering Transactions, 1978)
An approximate method for calculating aerodynamic characteristics of bodies in hypersonic rarefied gas flow is set forth. It is based on assuming that the momentum flux p at the body surface is to be determined by the local incidence angle q1 irrespective of the body form. The p (q1)-approximation contains a number of empirical coefficients depending on regime parameters. As a result the problem is split into two parts: first calculating form functions independent of the flow regime and, second finding regime coefficients independent of the body form. Treatment with experimental data has shown the local approach to be sufficiently exact for all Knudsen numbers. An extension of the method to finite Mach numbers is also proposed. Some advisable trends towards the further development of the local theory are discussed.